SURFACE TEMPERATURE DISTRIBUTION ANALYSIS USING REMOTE SENSING SYSTEM IN SPERMONDE ESTUARY - Rakhmad Armus; Alfian Noor; Ahyar Ahmad; Muhammad Lukman (Hasanuddin University, 2018)
Research on the phenomenon of climate change on the region Makassar Strait waters that are part of the oceanographic activities that require observation of the sea surface temperature (SST), surface currents and ocean color imagery from satellite imagery. In this case, satellite remote sensing data using Aqua-Modis analyze both visually and raw-surface temperature parameter data in order to study a variety of other related phenomena that take place in the ocean. The existence of satellite imagery data for the observation of parameters and / or oceanographic phenomena will be more profitable in terms of time and cost and high accuracy. The purpose of this study was to review based on the description of the SST analysis using Aqua-Modis image data (non-commercial) and open source software in providing the information cepatdan applicable. Bodies Spermonde been considering the seas is quite unique because it is located right in the path of the current meeting of the Pacific Ocean through the sea of Sulawesi and spacious enough for the continuity of mesoscale oceanographic processes for coverage in the waters Spermonde in (islands) Indonesia